Penggunaan Media Teks Bergambar Dalam Meningkatkan Kemampuan Membaca Siswa Tunagrhita Kelas III DI SLB Negeri 1 Gowa - Muh Syarif Hidayatullah; Hadis Hadis; Triyanto Pristiwaluyo (JURNAL ORTO DIDAKTIKA, 2023)
This study examines the reading ability of third grade mentally retarded students at SLB Negeri 1 Gowa using pictorial text media. The formulation of the research problem is